Analyzing Factors Affecting the Effectivity of Faekhu Bus Station Operation - Berkat Buulolo; Suwardi Lubis; Dwi Lindarto (International Journal Labs, 2023)
Bus station is a public service provided by the government for the community. Therefore, the use of the bus terminal must be effective. This study aims to analyze the factors that influence the effectiveness of the use of Faekhu Bus Station which include government policies, facilities, government accessibility and government convenience. This study used the quantitative approach using a sample of 100 people. The data collection techniques were questionnaires and documentation using primary and secondary data. The data analysis technique was the multiple linear regression analysis test. The results showed that government policy had a positive and significant effect on the effectiveness of using Faekhu Bus Station, facilities had a positive and significant effect on the effectiveness of using Faekhu Bus Station, accessibility had no positive effect on effectiveness the use of the Faekhu Bus Station, and the convenience of the have a positive and significant effect on the effectiveness of the use of the Faekhu Bus Station.